UK Khat Prohibition and the Making of a Harmful Drug - Guntars Ermansons (Medicine Anthropology Theory, 2024)
This article delves into the complex dynamics of khat (Catha edulis) prohibition in the UK, with a particular focus on a Somali community in north-west London. Despite the Advisory Council on the Misuse of Drugs finding no substantial evidence of khat causing societal or medical harms and recommending public health interventions instead of prohibition, the UK Home Office classified khat as a Class C drug in June 2014. This decision raises critical questions about what constitutes a harmful drug. Based on ethnographic fieldwork conducted during the peak of prohibition discourse in 2013–14, the article explores how notions of harm operate across moral, political, and epistemological registers as people grapple with framing khat’s drug status and the effects of its use. It illustrates how prohibition discourse not only amplified perceptions of khat’s harmfulness but also sidelined the more nuanced concerns of Somali community members over persistent socioeconomic integration issues, mental health, and social marginalisation. Thus, the harm of khat may not lie in its potency as a psychoactive substance but as an object of prohibition that overshadows interventions to address the adverse conditions associated with its use among certain individuals.